A Public Health Approach to Reducing the Societal Prevalence and Burden of Youth Mental Health Problems: Introduction to the Special Issue. Issue 1 (28th November 2020) - Herman, Keith C.; Reinke, Wendy M.; Thompson, Aaron M.; M. Hawley, Kristin; Wallis, Kelly; Stormont, Melissa; Peters, Clark
Abstract: The purpose of this Special Issue is to describe innovative school-related initiatives to reduce the population prevalence of youth mental health concerns. In this introduction to the Special Issue, we identify strategies that have not worked as well as those that have promise in improving youth mental health outcomes. We then provide a brief overview of each article in this issue. The first several articles focus on a comprehensive countywide approach to child and youth mental health that developed out of a unique tax initiative. In combination, these projects screen school-age youth in the county three times a year; support all county schools in providing universal, selective, and indicated interventions based on these screening data; deliver a mentoring program and school-based psychiatric care to youth with more intensive needs; and provide no-cost evidence-based evaluations, referrals, and ongoing progress monitoring to any family with concerns about their child's mental health. Three additional articles in the Special Issue expand the focus to include other national models, including a statewide initiative in Georgia to bring mental health services to every school, policy issues related to school mental health in South Carolina, and cost analysis strategies for specifying the economic benefit of mental health initiatives.